Հայաստանի ազգային պատկերասրահի հայկական ֆոնդի ձևավորման ու համալրման խորհրդային փորձը. 1920-1930-ական թթ. - Նազարյան, Անի
Հոդվածի շրջանակներում Հայաստանի Ազգային պատկերասրահի օրինակով դիտարկել ենք, թե Խորհրդային գաղափարախոսությունն ու կենտրոնական կառավարման համակարգն ի՛նչ առաքելություն էին նախատեսում նորաստեղծ թանգարանի համար և այդ ամենն ինչպե՛ս էր արտահայտվում թանգարանային հավաքածուների ձևավորման ու տեսականու համալրման գործում։ В рамках статьи на примере Национальной галереи Армении, мы рассмотрим какую миссию подготовила советская идеология и система центрального правительства для вновь созданного музея, и как это отразилось на пополнении музейных коллекций. Вдохновленные идеей о создании Национального музея на родине, многие деятели искусства диаспоры посчитали своим долгом участвовать в процессе сбора коллекции. Благодаря их щедрым пожертвованиям армянский фонд Национальной галереи Армении пополнился произведениями разных жанров изобразительного искусства. Соответственно, мы обсудим деятельность ведомственных и профессиональных структур, направленных на пополнение музейной коллекции, участие деятелей искусства диаспоры в процессе создания музея и обогащения коллекций. В результате этого мы будем описывать произведения искусства, хранящиеся в Армянском фонде музея, по жанрам, темам и по авторам. Based on the example of the National Gallery (henceforth the NGA), the article explores the influence of the Soviet ideology and the central governing system on the newly established museum, its mission as well as its culturaleducational operations. Three crucial factors are identified in the process of the formation and expansion of the Artistic Division of the museum in the context of the historical development of the latter: the role and characteristics of state institutions (ministerial), professional bodies (artistic unions) and individuals (artists, creative and art-loving citizens). Not surprisingly, establishing a wide network of museums in the Soviet republics became one of the peculiarities of the cultural policy of the Soviet state. Museums were declared a means to spread and publicize the socialist ideology stemming from the cultural policy of the authorities as a result of which cultural life was strictly controlled and politicized. In this context, museums were transformed from scientific-cultural entities into political-educational institutions.
Keywords: Մշակույթ